2016
DOI: 10.1371/journal.pone.0150088
|View full text |Cite
|
Sign up to set email alerts
|

Health Service Utilization among Syrian Refugees with Chronic Health Conditions in Jordan

Abstract: IntroductionThe influx of Syrian refugees into Jordan presents an immense burden to the Jordanian health system, particularly in treating chronic health conditions. This study was undertaken to assess utilization of health services for chronic health conditions among Syrian refugees in non-camp settings.MethodsA survey of Syrian refugees in Jordan was undertaken in June 2014 to characterize health seeking behaviors and issues related to accessing care for hypertension, diabetes, cardiovascular diseases, chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 2 publications
4
89
0
Order By: Relevance
“…The literature suggests that noncommunicable diseases among Syrian refugees in Jordan posed the highest burden on the Jordanian health care system. 19,20 It has been reported that refugees are at risk for deteriorating mental and physical health soon after arriving in Canada. 17,21,22 Our findings on unmet health care needs suggest a course toward this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that noncommunicable diseases among Syrian refugees in Jordan posed the highest burden on the Jordanian health care system. 19,20 It has been reported that refugees are at risk for deteriorating mental and physical health soon after arriving in Canada. 17,21,22 Our findings on unmet health care needs suggest a course toward this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Such families may decide to forgo health care services because of the cost, especially for chronic conditions that may be considered as less urgent (or requiring less care) in the short term. 9 The health care sectors in Jordan function independently, and there is no national electronic health records system. The availability of electronic patient records and the utilization of electronic prescribing are not universal in Jordanian hospitals.…”
Section: Health System Leadership Governance and Health Care Financingmentioning
confidence: 99%
“…Research has focused on isolated issues that have affected the health of Syrian refugees in neighbouring countries, such as health service access and utilization (8,9), the prevalence of chronic conditions among certain refugee age groups (10), the prevalence of infectious diseases among refugees, and the psychosocial and mental health care shortcomings. However, research on how refugees prioritize these issues that affect their health is scarce.…”
Section: Introductionmentioning
confidence: 99%